An analysis of fishermens happiness during the COVID-19 pandemic - Mustikasari, Indri; Tain, Anas; Damat, Damat (Universitas Malikussaleh, 2024)
Happiness can be interpreted as subjective well-being that elucidates about the meaning of life, feeling, and overall life satisfaction. According to FAO, Covid-19 pandemic impacts on global food supply chain. So far, the concept of happiness and the welfare of coastal communities does not get the appropriate portion. This study aims to: (1) analyze the happiness level of fisherman during Covid-19 pandemic, (2) analyze the influence of the dimensions of life satisfaction, feelings, and the meaning of life on the fishermans happiness during the covid-19 period, and (3) analyze the differences to the fishermans happiness based on fishing fleet structure. This study was a descriptive study using quantitative approach. There were 107 fishermen of Prigi Archipelagic Fishing Port (PPN) used as the subjects of study. Sampling technique used stratified random sampling by noticing to the ship fleet size strata. The data of this study referred to enumeration guidelines of happiness level measurement survey (SPTK) by Statistic Center and Oxford Happiness Questionnaire (OHQ). Generally, the fishermen who are at the PPN Prigi area is in the quite happy category. The satisfaction, feeling, and meaning of life dimensions significantly influence the fishermans happiness during the Covid-19 pandemic. Based on the obtained score, the highest happiness level ison the fisherman who have the type of fleet of 10-2- GT vessels, in which it is 4,11; the type of fleet <10 GT is 4,1; and the vessel fleet of 20 GT is 4,03: and there is no difference in the fishermans happiness based on structure of the fishing fleet.Keywords: BPS Measurement, Covid-19, Fishermen; Happiness, OHQ Measurement